Negociando o comum e buscando diferenças das performances de gênero nas experiências de mulheres no consumo de bebidas alcoólicas - Thais Santos Silva (2018)
When entering a traditionally masculine environment, the alcohol experience of women requires the negotiation of behaviors and concepts of masculinity and femininity consolidated. As a social experience, this consumption is influenced by social and cultural norms and must be analyzed beyond the perspective of disease. In this sense, the objective of this study was to identify and analyze the relationship between compliance with established social norms on women's and men's roles and the aspects that make up the social experiences of women's alcohol consumption. The Conformity for Feminine and Masculine Norms Inventory (CFNI-45 / CMNI-29), validated for the Brazilian reality, and the theoretical model of consumer experiences proposed by Lanier and Rander (2015) were used. Since the authors' proposal is generic, the application to the objectives of this research required the development of the constitutive variables of each of the four experiences: performance experience / stochastic experience / liberating experience / adventure experience, established through a qualitative survey, previous to a survey of the work with 551 women consuming alcoholic beverages. The results, analyzed through the Modeling of Structural Equations and the Hierarchical Analysis of Grouping, supported the typological structure of experience used and found significant effects of normative conformities for men and women under the experiences of alcohol consumption of women. The women were grouped into three groups from their compliance with the norms: Group 1 with mean greater masculine conformity and intermediary feminine conformity; Group 2 with mean intermediary masculine conformity and mean highest in feminine conformity; Group 3 with women with mean responses of the two indicators smaller than the other groups. In addition, the variables marital status and age were relevant in these groups. Unaccompanied women were more compliant with male norms and less compliant with women's norms, which may reveal the smoothing of existing normative female standards and the endorsement of experiences of alcohol consumption by women